The natural increase of the population of Dohuk Governorate for the period (2007-2017) and its spatial variation - M. Hasan, Chinar (Academic Journal of Nawroz University, 2021)
The study entitled ((Natural increase of the population of Dohuk governorate for the period (2007-2017) and its spatial variation)) aims to show the rates of natural increase, i.e. the difference between births and deaths in Dohuk governorate according to districts after the governorate witnessed a noticeable increase in recent years, which required us to find out. The research consisted of three sections: the first topic dealt with the extraction of the crude birth rate, the second topic examined the crude death rate, and the third topic examined the rate of natural (vital) increase during the period according to the administrative units, and the study concluded that the rate of natural increase in Dohuk governorate It decreased from (3.3%) in 2007 to (2.1%) in 2017.